Network Asymmetries and Access Pricing in Cellular Telecommunications - Viktória Kocsis (Tinbergen Institute, 2005)
Network shares and retail prices are not symmetric in the telecommunications market with multiple bottlenecks which give rise to new questions of access fee regulation. In this paper we consider a model with two types of asymmetry arising from different entry timing, i.e. a larger reputation for the incumbent and lower cost of servicing for the entrant as a result of more advanced technology. As a result firms have divergent preferences over the access fee. In case of linear and non-linear prices the access fee might still act as the instrument of collusion, but only if a side-payment is permitted which is generally welfare decreasing. Moreover, in contrast with the European regulatory framework, the access fee on the basis of termination cost might not necessarily be a socially preferable solution.
Keywords: L11; L13; L51; L96; 330; cost asymmetry; brand loyalty; imperfect competition; network interconnection; access fee